Simulation of Van Allen Probes plasmapause encounters. Issue 9 (23rd September 2014) - Goldstein, J.; Pascuale, S. De; Kletzing, C.; Kurth, W.; Genestreti, K. J.; Skoug, R. M.; Larsen, B. A.; Kistler, L. M.; Mouikis, C.; Spence, H.
Abstract We use an E × B‐driven plasmapause test particle (PTP) simulation to provide global contextual information for in situ measurements by the Van Allen Probes (Radiation Belt Storm Probes (RBSP)) during 15–20 January 2013. During 120 h of simulation time beginning on 15 January, geomagnetic activity produced three plumes. The third and largest simulated plume formed during enhanced convection on 17 January, and survived as a rotating, wrapped, residual plume for tens of hours. To validate the simulation, we compare its output with RBSP data. Virtual RBSP satellites recorded 28 virtual plasmapause encounters during 15–19 January. For 26 of 28 (92%) virtual crossings, there were corresponding actual RBSP encounters with plasmapause density gradients. The mean difference in encounter time between model and data is 36 min. The mean model‐data difference in radial location is 0.40 ± 0.05 RE. The model‐data agreement is better for strong convection than for quiet or weakly disturbed conditions. On 18 January, both RBSP spacecraft crossed a tenuous, detached plasma feature at approximately the same time and nightside location as a wrapped residual plume, predicted by the model to have formed 32 h earlier on 17 January. The agreement between simulation and data indicates that the model‐provided global information is adequate to correctly interpret the RBSP density observations.